Simulation Study Effect of Fine Particle on Choke Valve by Using Computational Fluid Dynamic (CFD) - Zul Azri, Azril Danial (IRC, 2016)
Erosion has cause a lot of challenge in oil and gas industry nowadays. There is a lot of criteria that could increase the impact of erosion to the pipeline system. The example of criteria that could speed up the impact of erosion are Speed of particle, type of particle, impact angle and etc. There are two main objective of this research which are to develop the simulation model and investigate erosion due to the effect of fine sand particle on Choke Valve at different valve opening. Numerical simulation was performed by using CFD software ANSYS-FLUENT. This researched consist of 4 type cases which are tee-joint without valve, tee-joint with 10 percent opening valve, tee-joint with 50 percent opening valve and tee-joint with 100 percent opening valve. This research consist of 2 main control variable which are speed (5m/s, 10m/s and 15m/s) and pressure (40 Bar, 45 Bar and 50 Bar). The effect of 1 micron size of particle has being tested in the simulation. A comparison of erosion result at different valve opening was being explained in this researched. The simulation result revealed that highest erosion rate is 4.38196×10−6